THE SOCIO-ECONOMIC CONTRIBUTION OF SMALL-SCALE INDUSTRIES TO LIVELIHOOD OF WOMENIN THE SHEA BUTTER INDUSTRY IN THE WA MUNICIPALITY - Simon, Kanlisi Kaba; Rudolf Junior, Amenga-Etego; Okyere, Akomeah Daniel; Robert, Amoako; Elvis, Narh (European Scientific Journal, ESJ, 2014)
The Shea tree, which is now referred to as’VitellariaParadoxa’, has enormous economic, medicinal, cultural benefits and as a food source. Yet it seems the mechanisms put in place to support the Shea butter industryare either not existing or they are inadequate in Ghana.Even though this is the general situation,the quantum of the industry’s contribution to women livelihood, the specific social and economic effects and the mechanisms created to support women in the industry are yet to be empirically investigated in the Wa Municipality of the Upper West Region.The study therefore sought to address what the contribution of the Shea butter processing industry in promoting the socio-economic development of women and their livelihood has been in the Wa Municipality, the nature of the social and economic effects on the livelihood of women; the specific mechanisms put in place as support for women in the industry as well as the nature of the industry’s prospects and challenges in Wa Municipal area.A case study approach was adopted.The research revealed that only women areemployed in the Shea butter processing industry. The studyalso revealed that there are few organizations providing financial and technical support to the women in Shea butter production in the Wa Municipality. Through Shea butter processing, the women have secure employment which provided them with income for the satisfaction of their basic needs. Ready market was identified as a major constraint. The intensive use of firewood produced wood smoke which caused respiratory infections such as severe cough, lung infections, running nose, nasal congestion, headaches, low-grade fever, sneezing, and optical disorders among the women.